Identification of polymorphisms of XRCC1 gene in patients with cancer in a city of northern Brazil - Artemis Socorro N. Rodrigues; Tainá L. Vanzeler; Gabriel O. Espíndola (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACT Introduction: Cancer is considered a genetic disease. For this reason, identification and characterization of the genes involved in its origin and progression are of fundamental importance in understanding its molecular basis. Objective: Our objective was to determine whether people from Macapá with a diagnosis of cancer have genetic polymorphisms related to the XRCC1 gene. Materials and methods: We analyzed 30 samples of deoxyribonucleic acid (DNA) of cases with cancer and 30 control samples. All samples were amplified and analyzed by the polymerase chain reaction-restriction fragment length polymorphisms (PCR-RFLP) method, with the use of restriction enzyme MspI. Results: Regarding the 194T polymorphism, we found that all samples of the cases presented the polymorphic allele Trp (Arg/Trp). In control samples, 96.6% also identify the polymorphic allele Trp and, among these, one was homozygous for the same allele (Trp/Trp). Regarding the 399A polymorphism, 83.3% of the cases and 23.3% of the controls had the Arg/ Gln genotype, respectively. We found that 73.3% of controls and 16.6% of cases had the Arg/Arg genotype. Among the controls, we found only a sample that was homozygous for the polymorphic allele Trp/Trp. Conclusion: Our results demonstrated the allele frequency of 194Trp polymorphism in both sample groups analyzed. We also found a significant number of polymorphic allele 399A in people with cancer. Thus, we can highlight 399Gln polymorphism as a genetic marker of cancer risk in this population.